Impact of renal function on eligibility for chemotherapy and survival in patients who have undergone radical nephro‐ureterectomy. (6th March 2013) - Xylinas, Evanguelos; Rink, Michael; Margulis, Vitaly; Clozel, Thomas; Lee, Richard K.; Comploj, Evi; Novara, Giacomo; Raman, Jay D.; Lotan, Yair; Weizer, Alon; Roupret, Morgan; Pycha, Armin; et al.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Radical nephroureterectomy (RNU), the standard of care treatment for high‐risk urothelial carcinoma of the upper tract (UTUC), results in loss of a renal unit. Loss of renal function decreases eligibility for systemic chemotherapies and results in decreased overall survival in various malignancies. The study shows that only a small proportion of patients had a preoperative renal function that would allow cisplatin‐based chemotherapy. Moreover, eGFR significantly decreased after RNU, thereby lowering the rate of cisplatin eligibility to only 16 and 52% of patients based on the thresholds of 60 and 45 mL/min/1.73 m2, respectively. Taken together with the rest of the literature, the findings of the study support the use of cisplatin‐based chemotherapy, when indicated, in the neoadjuvant rather than adjuvant setting. Objective To report (i) the estimated glomerular filtration rate (eGFR) changes in patients undergoing radical nephro‐ureterectomy (RNU) for upper tract urothelial carcinoma (UTUC); (ii) the rate of change in eGFR in patients eligible for cisplatin‐based chemotherapy; and (iii) the association of preoperative, postoperative and rate of change of renal function variables with survival outcomes. Patient and Methods We performed a retrospective analysis of 666 patients treated with RNU for UTUC at seven international institutions from 1994 to 2007. The eGFR was calculated at baseline and at 3–6 months (Modification of Diet in Renal Disease formula (MDRD) and Chronic Kidney Disease Epidemiology Collaboration formula (CKD‐EP) equations). Results The median (interquartile range) eGFR decreased by 18.2 (8–12)% after RNU. A total of 37% of patients had a preoperative eGFR ≥ 60 mL/min/1.73 m2, which decreased to 16% after RNU (P < 0.001); 72% of patients had a preoperative eGFR ≥ 45 mL/min/1.73 m2, which decreased to 52% after RNU (P < 0.001). The distributions were similar when analyses were restricted to patients with locally advanced disease (pT3–pT4) and/or lymph node metastasis. Patients older than the median age of 70 years were more likely to have a decrease in eGFR after RNU (P < 0.001). None of the renal function variables was associated with clinical outcomes such as disease recurrence, cancer‐specific and overall mortality; however, when analyses were restricted to patients who had no adjuvant chemotherapy and did not experience disease recurrence (n = 431), a preoperative eGFR ≥ 60 mL/min/1.73 m2 (P = 0.03) and a postoperative eGFR ≥ 45 mL/min/1.73 m2 (P = 0.04) were associated with better overall survival in univariable analyses. Conclusions In patients who had UTUC, eGFR was low and furthermore, it significantly decreased after RNU. Renal function did not affect cancer‐specific outcomes after RNU.